View Single Post
Old 2020-02-25, 08:21   #8
Nick's Avatar
Dec 2012
The Netherlands

7×239 Posts

Originally Posted by wildrabbitt View Post
Also, in case there's an obvious remedy to my latex not parsing properly, here's an example of what I wrote in the first post without the \\( and \\).

\sum_{n=1}^\infty \big(\frac{n}{q}\big)x^n=\frac{1}{1-x^q}\sum_{m=1}^{q-1}\big(\frac{m}{q}\big)x^m=\frac{xf(x)}{1-x^q}
LaTeX: just put backslash then open-square-bracket before it, and backslash then close-square-bracket afterwards:

\[\sum_{n=1}^\infty \big(\frac{n}{q}\big)x^n=\frac{1}{1-x^q}\sum_{m=1}^{q-1}\big(\frac{m}{q}\big)x^m=\frac{xf(x)}{1-x^q}\]
Nick is offline   Reply With Quote